Preoperative Conjunctival Swab Analyses for Chloramphenicol and Moxifloxacin in Normal Ocular Commensals - Sajeev Cherian Jacob; Isiri Revanasiddappa; Thirumagal Vaishnavi; CL Antony; Venkataramana Kalikivay (Delhi Journal of Ophthalmology)
Purpose:- Normal microfloras of conjunctival sac can flourish and be the potential cause for postoperative intraocular infections. Precautions and measures have to be taken to prevent acute postoperative endophthalmitis, which is a challenge to treat, and has poor visual outcome. Hence this study was done to assess the sensitivity of commonly used topical antibiotics like chloramphenicol and moxifloxacin. Material & Methods:- During the period of 10 months, 727 patients were included in the study that were either planned for intravitreal injection of anti-VEGF or were undergoing cataract surgery in a tertiary eye hospital. Conjunctival swabs were obtained, subjected to standard aerobic culture, along with identification techniques and antibiotic sensitivity evaluation was done. All collected data was entered in Microsoft Excel and statistical analysis was performed. Results:- Out of 727 conjunctival swabs, 13 (1.7 %) conjunctival swabs showed microbial growth. The most common organism was found to be staphylococcus epidermidis. Microbial culture and antibiotic sensitivity revealed that only 5 conjunctival swabs (38%) showed sensitivity to moxifloxacin, whereas chloramphenicol showed sensitivity in 11 conjunctival swabs (85%). The antibiotic sensitivity reports of inhibition zone for moxifloxacin and chloramphenicol were compared using paired t test and showed that bacteria were more sensitive to chloramphenicol than moxifloxacin with p value of 0.00. Conclusion:- The results of this study suggest that topical chloramphenicol was found to be more sensitive as compared to topical moxifloxacin. Hence, it is wise to choose the cheaper and more effective topical chloramphenicol over moxifloxacin.